The Role of Internal Audit in Analyzing and Auditing Big Data and its Impact on the Quality Financial Reports - Wahhab, Asaad Mohammed Ali; Alajeli, Emad Hamza Abd.; Jawad, Baneen Hassoun (Technium Social Sciences Journal, 2022)
The research aims to develop and raise the efficiency of audit programs for the internal audit function, which helps in auditing big data and reducing the company’s challenges and measuring the efficiency and effectiveness of internal auditing in light of big data to produce high-quality financial reports. To achieve these goals, 93 questionnaires were distributed to the internal auditors in 38 banks in Iraq and included two axes and several questions ( 24 ) to know the role of the internal auditor in auditing and analyzing massive data and the extent of the impact of this role on the quality of the financial reports of banks. Used spss program to analyze the data and the research found.